Kesiapan Perlindungan Merek Pelaku Usaha Menuju UMKM Unggulan di Kota Serang - Dwisvimiar, Inge; Syahrul Mucharom, Rully; Nurzahira, Anbar (Universitas Ekasakti, 2023)
The ease of access to trademark registration and the special treatment of reduced registration fees given to Micro, Small and Medium Enterprises have not made the employers register their brands as a form of preparedness towards legal protection of brands.The aim of this research is to analyze the readiness that must be met by Micro, Small and Medium Enterprises based on local food ingredients in legal brand protection and their efforts towards leading enterprises in Serang City. The research method used is the empirical normative method. The data sources used are primary and secondary data with data collection techniques in the form of field studies and literature and analyzed descriptively qualitatively. The research results show that the readiness of Micro, Small and Medium Enterprises in legal protection of brands is to prepare for trademark registration, fulfill the requirements and carry out trademark registration to obtain a brand certificate as proof of ownership of brand rights and obtain brand protection. The efforts of Micro, Small and Medium Enterprises towards excellence are by innovating in improving product quality, finding funding sources, using technology in product marketing, taking advantage of programs created by the government, and paying attention to legal aspects.